Antimicrobial effect of silver diamine fluoride (SDF) in arresting dentine caries of permanent teeth: A Systematic review [version 1; peer review: 2 approved] - Mamata Hebbal; Albandri Mohammed Alowid; Praveen Jodalli; Shahad Saad Alkait; Ghadeer Ghalab Almutairi; Fatimah Salim Almufarji (F1000Research)
Background Silver diamine fluoride (SDF) is recognized for its potent antibacterial properties and is commonly used in dentistry to treat carious lesions. This review aims to evaluate the antimicrobial effect of SDF on dentine caries in permanent teeth. The objective is to provide a comprehensive analysis of the existing literature to assess the efficacy of SDF in combating cariogenic flora within dentin lesions. Materials and Methods A systematic electronic search was conducted using Google Scholar, Cochrane Library, and PubMed databases to identify relevant studies published between January 2010 and September 2022. The search strategy focused on retrieving in vitro and in vivo studies assessing the antimicrobial effect of SDF on dentinal caries. The inclusion criteria encompassed studies that compared SDF with other antimicrobial agents, such as sodium fluoride varnish, potassium iodide, silver nitrate, chlorhexidine, plasma jet, and deionized water. The Cochrane Collaboration assessment tool was employed to evaluate the risk of bias in the included studies. Results Nine studies met the inclusion criteria, consisting of seven in vitro and in situ studies investigating the antimicrobial effect of SDF on dentinal caries, and two in vitro and in vivo studies examining its antibacterial effect on root caries. These studies collectively demonstrated the promising antimicrobial potential of SDF against cariogenic flora present in dentin lesions. However, variations in study design, methodology, and outcome measures were observed across the included studies. Conclusion The review underscores the significant antimicrobial efficacy of SDF in combating cariogenic bacteria within dentin lesions of permanent teeth. Despite the promising findings, there remains a lack of comprehensive understanding regarding the precise characteristics and mechanisms underlying the antimicrobial action of SDF, particularly concerning nano-silver. Future research, including long-term clinical trials, is warranted to elucidate optimal dosage regimens and therapeutic approaches for the routine application of SDF in managing dental caries.